Diaporthe orixae sp. nov., an endophytic species isolated from Orixa japonica in southern China - Lu, Qing-Tao; Zhang, Jing-Yi; Sun, Ya-Ru; Tang, Xia; Lu, Yong-Zhong; Zhang, Zhen (Phytotaxa, 2022)
In this study, a novel endophytic fungus, Diaporthe orixae, and a new host record of Diaporthe caryae were obtained from a medicinal plant, Orixa japonica in southern China. Phylogenetic analyses based on a combination of ITS, tef1-α, β-tub, cal, and his3 datasets confirmed that D. orixae is a distinct species, which is sister to D. sackstonii (BRIP 54669b). Diaporthe orixae sp. nov. differs from D. sackstonii in having larger conidiomata and smaller conidiogenous cells and alpha conidia on morphological examination. The new species and new host record are reported with taxonomic descriptions and illustrations.